Evaluation of the Islamic Religious Education Learning Process in the Implementation of the Curriculum of the Minister of Religion Number 183 and Number 184 of 2019 - Muhamad Khoirur Roziqin; Yoga Nofan Aditiya (APPLICATION: Applied science in Learning Research, 2022)
The newly implemented ministry of religion curriculum number 183 and number 184 of 2019 can encourage the education and learning process in Madrasas to be more dynamic, creative, and innovative. Curriculum changes make it clear that learning is a shared responsibility between teachers, principals, and education boards. In implementing the curriculum, the principal plays an important role because the principal is responsible for the schools he leads and is required to develop the professionalism of teachers and education personnel. Failure to implement this curriculum is caused by a lack of knowledge, skills and abilities of teachers in carrying out their duties. This condition shows that the function of the curriculum lies in its implementation in schools. Therefore, this study aims to obtain empirical evidence regarding the evaluation of the learning process of Islamic education in the implementation of the curriculum of the Ministry of Religion Number 183 and Number 184 at Al-Ihsan Kalikejambon Islamic High School Tembelang Jombang. This research is expected to be used as material for school considerations to build a religious culture as an effort to improve student discipline, and the results of this study can add to the literature and can be used as reference material for further research. The research method used is descriptive qualitative analysis. The data collection used is interviews, observation and documentation. Data collection in the field was carried out in 2021. The results showed that Al-Ihsan Kalikejambon Tembelang Jombang Islamic High School had not implemented the curriculum of the ministry of religion number 183 and number 184 in teaching this year. But in the future the institution will implement the curriculum.